Authenticity as a sustainable value of holistic conservation: The case of Turkey's world heritage sites - Özlem Karakul (Megaron, 2016)
The discussions on ‘authenticity' have always been central in conservation studies. Nowadays, in recent years, the discussions also continued within the debates on the conservation of intangible cultural heritage. This paper brings a new standpoint about ‘authenticity', considering it as a value for conservation. Its subjective nature need to be minimized by the clear definition of its constitutive aspects including both tangible and intangible features. To make it more concretized, it needs to understand the decision makers on authenticity and to define it in current conditions of historic environments comparatively. Before the Nara Document on Authenticity, defining the concept of authenticity as 'the essential qualifying factor concerning values', it had generally been explained as a quality regarding physical characteristics. The document determined the sources of information to be linked with authenticity including 'form and design, materials and substance, use of function, traditions and techniques, location and setting, and spirit and feeling, and other internal and external factors'. After this document, the relations between intangible values and authenticity have been tried to be defined more clearly. This study puts forward that the sustainability of the originality of integrity of both intangible and tangible values is significant for the accuracy of the holistic conservation of built heritage. The study mainly investigates two of Turkey's sites in the world heritage list (WHL), Archeological Site of Troy and City of Safranbolu, considering their outstanding universal value and the related criteria which they satisfied; and, the tangible and intangible aspects of their specific conditions of authenticity as outlined in the Nara Document on Authenticity comparatively.